Kwestia europejska w programach polskiej lewicy po 1989 roku. Przegląd stanowisk - Małysa, Krzysztof (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
The article presents a discussion conducted pertaining to Poland’s place in Europe, and European conceptions in political thought in the left wing parties. The left supported the process of European integration with the exception of the Polish Communist Party. Now, the left stand for an inclusive society based on principles of equality, freedom and solidarity. The left’s vision is for an idea of a social Europe. So, the left postulates a new European economic strategy to create sustainable development, protect social rights and guarantee universal access to social security.
THE EUROPEAN QUESTION IN THE PROGRAMMES OF POLISH LEFT WING PARTIES AFTER 1989. A REVIEW OF THE SITUATION
Keywords: The left wing parties; integration; social Europe; federation